An Improved Medical DR Image Enhancement Method - Bi Juntao (Institute of Advanced Engineering and Science, 2014)
As a result of noise interference, improper exposure and thick human tissue, detail information of DR image will be buried, including unclear edge and contrast reduction. This paper proposes a medical DR image enhancement processing based on artificial fish-swarm algorithm. According to DR image contour model and DR image boundary, the enhancement processing segment DR image by artificial fish-swarm clustering method, then enhance DR classification image through adding GAG operator. Simulation results show that the method can effectively eliminate noise in DR image, and the detail information of enhanced DR image is clearer than before meanwhile with high effectiveness and robustness. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4305